2022
DOI: 10.3390/ani12020138
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Development of Three Former Pet Chimpanzees a Decade after Arrival at the MONA Sanctuary

Abstract: Chimpanzees used as pets and in the entertainment industry endure detrimental living conditions from early infancy onwards. The preferred option for ending their existence as pet or circus chimpanzees is their rescue and transfer to a primate sanctuary that will provide them with optimal living and social conditions, so that they can thrive. In this case study, we had the rare opportunity to compare the activity budgets of three chimpanzees from their time as pets in 2004 to their time living at the MONA sanct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…We also found that nursery-reared chimpanzees tended to be more submissive than those who were mother reared. This was expected, given previous findings that nursery-reared chimpanzees display more submissive and less prosocial behavior in social settings and that early deprivation may have lasting effects on chimpanzee social behavior [ 23 , 24 , 27 , 40 , 70 , 71 ]; but in contrast, see [ 72 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We also found that nursery-reared chimpanzees tended to be more submissive than those who were mother reared. This was expected, given previous findings that nursery-reared chimpanzees display more submissive and less prosocial behavior in social settings and that early deprivation may have lasting effects on chimpanzee social behavior [ 23 , 24 , 27 , 40 , 70 , 71 ]; but in contrast, see [ 72 ].…”
Section: Discussionmentioning
confidence: 97%
“…Although there are few articles that discuss the deaths of chimpanzees during social integrations, and they are rare, they do occur (first author, personal experience; S. Ross, personal communication). However, most group formations of chimpanzees do have successful outcomes with observed affiliative behavior, which may be one of many possible indicators of a successful introduction [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infant chimpanzees spend their first two to five years close to their mothers [14,58,59], developing their social skills by interacting with their mother and other members of their group [14], learning and acquiring speciestypical behaviors [60], which includes acquiring social capacities to navigate social complex networks. However, many chimpanzees with a past as pets, entertainers or laboratory animals did not experience such an upbringing [61]. During the second half of the 20th century, thousands of infant chimpanzees were captured from the wild [62,63], typically resulting in early maternal loss [64,65], prolonged social isolation [66] and the lack of social partners during their first years of life [67,68].…”
Section: Introductionmentioning
confidence: 99%
“…Japanese scientists have looked at cortisol levels and the effects of relocation [ 20 ] as well as social play as an indicator of positive welfare [ 21 ]. The Fundacio Mona Centre de Recuperacio de Primats sanctuary in Spain has focused on the rehabilitation and resocialization of their chimpanzees [ 22 ] as well as their development over time [ 23 ]. Chimfunshi, a sanctuary in Africa, has studied differences between chimpanzees removed from their mothers at early ages with those who were born and raised in the sanctuary [ 24 ].…”
Section: Introductionmentioning
confidence: 99%